EU investigates Musk's X, as harmful content surges from Israel-Hamas war - O'Brien, Peter (France 24, 2023)
The European Commission has opened an investigation into X, Elon Musk's social media platform formerly known as Twitter. The move comes after Brussels ordered X, as well as rivals Meta and TikTok, to act quickly to tackle the spread of disinformation, which has surged on each of these platforms since Hamas's deadly attack on Israel.
Keywords: 2023-10 October